A new approach of distribution system reconfiguration for loss minimization - Kashem, M. A.; Jasmon, G. B.; Ganapathy, V. (ELSEVIER SCI LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND, 2000)
Feeder reconfiguration for loss minimization is a network optimization problem and the solution for the problem involves a search over the configuration. This paper presents a systematic feeder reconfiguration technique that develops an optimal switching scheme to achieve a maximum reduction of losses in a distribution network. The technique restructures the distribution feeders by changing the open/closed status of the sectionalizing and tie switches. A minimal tree-search is proposed in this paper to find the possible switching-options for loss reduction. A loss change formula has been derived and used to determine the switching option that gives the maximum loss reduction in the system. The proposed technique can identify the most effective switching-options for loss reduction, and can achieve minimum loss configuration with minimum computational effort. The performance of the proposed technique is tested on a 33-bus system and the results are compared with that of Baran and Wu's method [Baran ME, Wu FF. Network reconfiguration in distribution systems for loss reduction and load balancing.IEEE Trans. Power Delivery, 1989;4(2):1401-1407]. (C) 2000 Elsevier Science Ltd. All rights reserved.